Heterozygote detection in angiokeratoma corporis diffusum (Anderson-Fabry disease). Studies on plasma, leucocytes, and hair follicles - Spence, M W; Goldbloom, A L; Burgess, J K; D'entremont, D; Ripley, B A; Weldon, K L (Journal of medical genetics, 1977)
Heterozygote detection for angiokeratoma corporis diffusum (Anderson-Fabry disease, ACD), an X-linked disorder of glycosphingolipid metabolism was examined using alpha-galactosidase activity, an alpha-galactosidase/beta-galactosidase activity ratios (alpha/beta ratio) in leucocytes, plasma, and hair follicles; For leucocytes, 22 obligate heterozygotes, 25 suspected heterozygotes, and 47 control subjects were studied, while for plasma, the groups were 17 obligate heterozygotes and 35 controls. The alpha/beta ratio in plasma and leucocytes was clearly a better discriminator between obligate heterozygotes and controls than alpha-galactosidase activity alone, but still failed to detect 3 obligates with leucocytes and 2 with plasma. Discrimination was not improved by joint use of plasma and leucocyte alpha/beta ratios, but was improved by measurement of hair-follicle alpha/beta ratios. The interdecile range of log (alpha-galactosidase/beta-galactosidase activity) in 20 hair follicles from each of 4 obligate and 7 suspected heterozygotes was clearly different from 11 control subjects. Accordingly, for rapid screening for carriers of ACD, we recommend use of leucocyte or plasma alpha/beta ratios which should detect greater than 85% of heterozygotes. When results are equivocal, and ancillary information suggests heterozygous status, the more time-consuming measurement of hair-follicle alpha/beta ratios is a useful additional test.